Analyzing Court Decisions on Interfaith Marriage: A Maqasid Sharia Perspective - Putri, Allysa Novita; Nur, Iffatin (Universitas Islam Sultan Agung, 2022)
The aim of this research is to analyze court decisions on interfaith marriages, specifically the decisions numbered 916/Pdt.P/2022/PN. Sby and 71/Pdt.P/2017/PN. Bla. This research uses a qualitative method with a normative juridical approach. The data in this study are digital data. The results of this research show differences in the interpretation of Article 2 paragraph (1) of the Marriage Law. The Surabaya District Court's decision interprets Article 2 paragraph (1) of the Marriage Law as indicating that interfaith marriage is not prohibited. This leads to a legal vacuum that causes judges to use the explanation of Article 35 (a) of the Population Administration Law to permit interfaith marriages and Article 10 paragraph (3) of Government Regulation No. 9 of 1975 to provide a basis for the implementation of interfaith marriages. The Blora District Court's decision interprets Article 2 paragraph (1) to consider the validity of marriage based on the respective religions of the applicants. The analysis results based on the theory of maqasid al-shari'ah proposed by Jamaluddin Athiyah indicate that the decision from the Surabaya District Court does not show preservation, while the decision from the Blora District Court does show preservation. The analysis based on Islamic legal methodology, maqasid al-shari'ah proposed by Jasser Auda, shows that both decisions do not fully meet the standards of the system approach.